Mechanical Properties of Concrete Specimens Containing Steel Fiber - Fong, Foo Mei; Masni Majid (Recent Trends in Civil Engineering and Built Environment, 2021)
In industry application, the steel reinforced are needed to carry the tension forces in the concrete. The problems that had been faced are cracking occurring in concrete and can the steel fiber control the cracking.This study describes an experimental analysis on grade 30 concrete mixtures by adding steel fiber with different percentages. The purpose of this research is to identify the mechanical strength and also the controlling of cracking that occurs in the concrete by adding steel fiber. Two types of mechanical properties are tested for the concrete specimen and they are the compressive strength test and the flexural strength test. Total of 16 cube samples will be carried out for compressive strength testing and 6 prisms for flexural strength by applying 0 %, 0.1% and 0.3 % of steel fiber to the concrete sample for flexural strength. The curing method that been used in this experiment is water curing for 7 days and 28 days. The concrete specimen size that been used for compressive strength test is 100mm x 100mm x100mm cube and for flexural strength test is 1000mm x 150mm x 100mm. In this experiment, 22 of concrete specimens were cast and tested. Based on compressive strength test, for 7 days and 28 days shows different increment valueof compressive strength. Control shows the less compressive strength compare to 0.1% and 0.3% of steel fibre. During flexural test for control prism, the maximum load had been applied before it fails is 9.62 kN for sample 1 and 9.67 kN for sample 2. The maximum load applied for steel fibre containing 0.1% to reach its failure for sample 3 is 12.02 kN, sample 4 is 12.25 kN and for 0.3% of steel fibre sample 5 is 13.24 kN and sample 6 is 13.11 kN. The result form this research shows that by adding steel fibre into the concrete, the mechanical strength can be increased, and it can delay the cracking.